Reflexões sobre projeto de vida e sua construção: a contribuição da filosofia existencialista de Sartre junto aos alunos do ensino médio - Carneiro, Cleyton Gomes (2021)
The work situates the discussion in the fields of Sartre's existentialist philosophy and its contribution to the education of young people through the Discipline of Philosophy, as one of the points of the syllabus, for high school students who, being in the development phase, they need this discussion so that there is the possibility of their understanding of the ontological dimension of the self, the notions of freedom, ethics and human existence, for the purpose of understanding their own existence. In the beginning we will discuss ontology and existentialism in the historical context from the Sartrean point of view, as well as its main categories: freedom, being-in-itself, being-for-itself, being-with-others; understanding and articulating the fundamental concepts of existentialism, as a way of facilitating the understanding of the relationship between his thought and human formation with the challenge of existential resignification. Finally, as a methodology, we will make an analysis, through an open questionnaire, applied to high school students, to verify the extent to which Sartre's existentialist theory can contribute to their understanding of the aforementioned categories. In short, we aim to perceive / demonstrate how Sartrean existentialism, through the teaching of Philosophy at school, can contribute to reflection, awareness and to the student's choices and, consequently, to the construction of a moral and ethical base of their own actions.